Framing insiders by outsiders - Jackson, Glenna S. (HTS teologiese studies, 2019)
In this article, the author rehearses the Lukan parable of the Friend at Midnight (Lk 11:5–8) as a segue from Insiders and Outsiders and a Hermeneutic of Resonance to provide a method she employs as an outsider sharing stories from and insights into a culture in which she was not born. She then connects her personal and existential experiences to the academic world of research.